Pengaruh Penilaian Kinerja Dan Loyalitas SDM Terhadap Promosi Jabatan Pada PT BPR Hitamajaya Argamandiri - Bukhari Muslim; Diana Nurti Simanjuntak (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This research aims to examine the effect of Performance Appraisal (X1) and HR Loyalty (X2) on Position Promotion (Y) at PT BPR Hitamajaya Argamandiri. Data analysis was carried out using partial test and coefficient of determination test. The partial test results show that the Performance Appraisal variable (X1) has a T value of 3.102, which is greater than the T table of 1.69092 with a significance level of 0.004. with a significance level of 0.004. This also indicates that HR Loyalty (X2) has a significant effect on Position Promotion (Y), so the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted. The coefficient of determination (R²) test results show that the R² value is 0.384, which means that about 38.4% of the variability in Position Promotion (Y) can be explained by Performance Appraisal (X1) and HR Loyalty (X2), while the remaining 61.6% is influenced by other factors not included in this study. The research was conducted using quantitative methods with the research subjects being employees of PT BPR Hitamajaya Argamandiri. And the final results of this study concluded that both Performance Appraisal and HR Loyalty have a significant influence on Position Promotion at PT BPR Hitamajaya Argamandiri.